Paper on the subject of Burns's Pistols (Proceedings of the Society of Antiquaries of Scotland, 1862)
Bishop Gillis refutes the argument made by an anonymous author in the Illustrated London News who claimed that the two pistols he presented to the Society did not belong to Robert Burns. He first acknowledges that the pistols he had previously brought to the Society were a different set of pistols, that he had mistaken for Burns' pistols, as they were owned by the same person. He recounts the provenance of the correct pistols and disputes the anonymous author's claim that another set of pistols were the ones once owned by Burns.